Performance analysis of a communication system of 16/64 QAM modulation based on reconfigurable hardware: Performance of a communications system on reconfigurable hardware (Revista de Investigaciones Universidad del Quindío, 2014)
In this article, the performance of a baseband communications system of Quadrature Amplitude Modulation (QAM) implemented on a Field Programmable Gate Arrays (FPGA) is analyzed from the Bit Error Rate (BER) and the behavior of reconfigurable hardware. The baseband communications system considered an Additive White Gaussian Noise (AWGN) and the 16 QAM and 64 QAM modulations. It was designed through the Xilinx® System Generator® tool, was validated (at a simulation level) by means of a comparison with a model in Simulink® and was implemented on FPGA Spartan 6 of Xilinx® by downloading a programming file. As results, the basic performance curves of the baseband communications system of 16/64 QAM modulation were obtained and they were compared to the theoretical performance curves provided by the Matlab® Bertool® tool for its corresponding analysis. Thus, it was concluded that given the similarity of the performance curves obtained from System Generator®, Simulink®, implementation and Bertool®, the communication system achieved outstanding results upon reconfigurable hardware..
Keywords: Base Band Communications; FPGA; QAM Modulation; Reconfigurable Hardware; System Generator ®